Curriculum Design Automation for Sustainability Competency Training: An Approach Based on Genetic Algorithms - Franco, David Leonardo Molano; Castro, Juan David Forero; Tobar, Diego Xavier Rengifo; Valencia, Dagoberto Torres (Journal of Ecohumanism, 2024)
Sustainable development has positioned itself as a central axis in higher education, requiring the transformation of traditional curricular models towards structures that favor the formation of competencies in sustainability. This article proposes an innovative approach to automated curriculum design through the use of genetic algorithms, with the aim of optimizing the inclusion of content, methodologies and assessments focused on sustainability. Through an experimental study, a prototype system was designed that generates curricular proposals aligned with international sustainability standards and competency frameworks. The results show that the use of genetic algorithms allows a significant improvement in the coherence, flexibility and thematic coverage of the training programs. This research contributes to the efficient integration of sustainability in higher education through the use of computational intelligence.